Implementasi Murottal Ar-Rahman untuk Mengurangi Kecemasan pada Pasien Spinal Anestesi di Ruang Preoperasi RST Wijaya Kusuma Purwokerto - Rahmi Zahra Akyunin; Wilis Sukmaningtyas; Feti Kumala Dewi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Preoperative anxiety is a common psychological reaction in patients preparing for surgery, especially for those receiving spinal anesthesia, since they stay aware during the operation. Uncontrolled anxiety can adversely impact hemodynamic stability, raise anesthetic needs, and prolong postoperative recovery. Surah Ar-Rahman murottal therapy has arisen as a non-drug intervention that encourages relaxation and mental well-being. This research focused on assessing variations in preoperative anxiety levels after the application of Surah Ar-Rahman murottal therapy in individuals receiving spinal anesthesia. This community service initiative utilized an implementation method that involved a pretest–posttest framework with 30 elective surgical patients at RST Wijaya Kusuma Purwokerto from February to April 2026. Anxiety was assessed with the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Participants listened to a 10-minute audio rendition of Surah Ar-Rahman prior to surgery. Before the intervention, the majority of participants suffered from moderate anxiety (46.7%). After the intervention, most participants indicated mild anxiety (63.3%), 20.0% had no anxiety, and none were classified as severely anxious. The application of Surah Ar-Rahman murottal therapy significantly minimized preoperative anxiety and could act as a safe, supplementary non-drug approach in perioperative anesthesia nursing care.